Suhexiang pill for acute ischemic stroke in real-world practice setting (SUNRISE): protocol of a multicenter registry - Xinxing Lai; Xuejiao Xiong; Qi Jia; Tingting Liu; Zhaowen Yang; Chi Zhang; Lingbo Kong; Kegang Cao; Ting Dong; Caixia Fang; Jianwen Ge; Li Dong; et al. (BMC Complementary Medicine and Therapies)
Abstract Background Suhexiang (SHX) pill is widely used for treating acute ischemic stroke (AIS). Experimental and randomized controlled trials suggested that SHX pill was beneficial for patients with AIS. However, the effectiveness of SHX pill in real-world practice setting remains unclear. It is of great importance to investigate the effectiveness and safety of SHX pill in patients with acute ischemic stroke in real-world clinical practice with long-term follow-up. Methods The Suhexiang pill for acute ischemic stroke in Real-world Practice Setting (SUNRISE) is a multicenter, prospective, product-specific, observational study designed to provide insight into the administration of SHX pill for patients with AIS in the real-world clinical practice setting, with an initial sample size of 1000. Eligible patients treated with SHX pill within seven days of AIS onset will be consecutively included in this registry. The primary outcome is the proportion of patients independent at 3 months after stroke onset defined by an mRS score of 0, 1, or 2. Conclusion The findings of the SUNRISE registry will not only provide insights into the characteristics of patients who may benefit from SHX treatment, but also may enable the individualized treatment decision-making of SHX pill in real-world practice setting. Study registration This study was registered with the ClinicalTrials.gov (URL: https://clinicaltrials.gov/ , Unique identifier: NCT05833932).